Milton - Tillyard, E. M. W. (Writers and Their Work Series., 1972)
The poet John Milton (1608-1674) is best-known for writing Paradise Lost. In this 1952 study, E.M.W. Tillyard -- notable Shakespearian scholar, and an authority on Milton -- examines Milton's three major poems (Paradise Lost, Paradise Regained, and 'Samson Agonistes') alongside his masques 'Arcades' and Comus.